Flexural strength and fracture toughness of sea ice - Timco, G. W.; Frederking, R. M. W. (1983)
A series of mid-winter experiments were carried out on the ice in the rubble field around Tarsiut Island in the Beaufort Sea. The tests included grain structure determinations, salinity and density of the ice, small beam flexural strength and fracture toughness. Typical values for flexural strength and fracture toughness were 0.6 - 1.0 MPa and 100 - 140 kPa m[1/2] respectively. Both properties were dependent on brine volume and depth in the ice sheet. In comparing these results with identical tests on fine- grained freshwater ice it was found that for comparable loading conditions, the strength of the sea ice was significantly lower than the strength of the freshwater ice, whereas the fracture toughness of the sea ice was higher than the fracture toughness of the freshwater ice. On a effectué au milieu de l'hiver des expériences sur la résistance à la flexion et à la rupture de la glace qui se trouvait dans des champs de débris autour de l'île de Tarsiut dans la mer de Beaufort. Les essais comprenaient la détermination de la structure des cristaux, de la salinité et de la densité de la glace, et de la résistance à la flexion et à la rupture d'une petite poutre de glace. La résistance à la flexion était comprise entre 0,6 à 1,0 MPa et la résistance à la rupture entre 100 et 140 kPa.m[1/2]. Les deux caractéristiques dépendaient du volume d'eau salée à l'état liquide et de sa profondeur dans la couche de glace. En comparant ces résultats à ceux obtenus avec de la glace d' eau douce à fins cristaux, et pour des charges comparables, on a observé que la résistance à la flexion de la glace d' eau de mer était bien plus faible que celle de la glace d'eau douce tandis que la résistance à la rupture de la glace d'eau de mer était plus élevée. Peer reviewed: Yes NRC publication: Yes